INTERNAL TOURISM DEVELOPMENT STRATEGY INCREASING REGIONAL ORIGINAL INCOME (PAD) IN JAYAPURA CITY PAPUA PROVINCE - Fredrick Hendrick Mebri; Ermaya Suradinata; Kusworo Kusworo (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2022)
ABSTRACT. Regional Original Income (PAD) is an illustration of regional financial potential, where there are various sectors that can be developed to increase regional original income, one of which is the tourism sector, so that the existence of tourism is expected to be a contributor to regional original income, but the tourism sector in Jayapura City have not been managed and utilized optimally, in fact many tourism assets in Jayapura City are still controlled by customary rights owners by conducting illegal levies, lack of cooperative relationships with related agencies in building and developing tourist objects, and lack of community participation in developing tourist objects. Based on this, the authors are interested in conducting research with the title;